DCC mutation update: Congenital mirror movements, isolated agenesis of the corpus callosum, and developmental split brain syndrome. Issue 1 (11th November 2017) - Marsh, Ashley P. L.; Edwards, Timothy J.; Galea, Charles; Cooper, Helen M.; Engle, Elizabeth C.; Jamuar, Saumya S.; Méneret, Aurélie; Moutard, Marie‐Laure; Nava, Caroline; Rastetter, Agnès; Robinson, Gail; Rouleau, Guy; et al.
Abstract: The deleted in colorectal cancer ( DCC ) gene encodes the netrin‐1 (NTN1) receptor DCC, a transmembrane protein required for the guidance of commissural axons. Germline DCC mutations disrupt the development of predominantly commissural tracts in the central nervous system (CNS) and cause a spectrum of neurological disorders. Monoallelic, missense, and predicted loss‐of‐function DCC mutations cause congenital mirror movements, isolated agenesis of the corpus callosum (ACC), or both. Biallelic, predicted loss‐of‐function DCC mutations cause developmental split brain syndrome (DSBS). Although the underlying molecular mechanisms leading to disease remain poorly understood, they are thought to stem from reduced or perturbed NTN1 signaling. Here, we review the 26 reported DCC mutations associated with abnormal CNS development in humans, including 14 missense and 12 predicted loss‐of‐function mutations, and discuss their associated clinical characteristics and diagnostic features. We provide an update on the observed genotype–phenotype relationships of congenital mirror movements, isolated ACC and DSBS, and correlate this to our current understanding of the biological function of DCC in the development of the CNS. All mutations and their associated phenotypes were deposited into a locus‐specific LOVD (https://databases.lovd.nl/shared/genes/DCC ). Abstract : The deleted in colorectal cancer ( DCC ) gene encodes the netrin‐1 receptor DCC, a transmembrane protein required for the guidance of commissural axons. Mutations in DCC cause congenital mirror movements, isolated agenesis of the corpus callosum and developmental split brain syndrome. Herein, we review all reported DCC mutations associated with disease. We discuss the clinical and diagnostic features of each disorder, and correlate this to our current understanding of the biological function of DCC in the development of the human brain.